2022
DOI: 10.1108/jabes-06-2021-0076
|View full text |Cite
|
Sign up to set email alerts
|

The influence of market power on liquidity creation of commercial banks in Vietnam

Abstract: PurposeThis research examines the relationship between market power and liquidity creation in the specific context of bank profitability in the Vietnamese banking sector.Design/methodology/approachThe study applies the methodology proposed by Berger and Bouwman (2009) to demonstrate the creation of bank liquidity through a three-step procedure for investigating the relationship between market power and liquidity creation. The three steps include non-fat liquidity (NFLC), fat liquidity (FLC) and system generali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 85 publications
0
2
2
Order By: Relevance
“…Similarly, return has a negative and statistically insignificant effect, contrasting with the finding of Nguyen et al. (2022) who found a positive impact of profitability of banks on LC.…”
Section: Resultscontrasting
confidence: 80%
See 1 more Smart Citation
“…Similarly, return has a negative and statistically insignificant effect, contrasting with the finding of Nguyen et al. (2022) who found a positive impact of profitability of banks on LC.…”
Section: Resultscontrasting
confidence: 80%
“…This may be possible because of multi-collinearity due to the high correlation between risk and return explained earlier. Similarly, return has a negative and statistically insignificant effect, contrasting with the finding of Nguyen et al (2022) who found a positive impact of profitability of banks on LC. Now we come to the role of bank ownership in the LC channel of monetary transmission.…”
Section: Resultscontrasting
confidence: 74%
“…On the other hand, inflation adversely affects bank growth since it increases the price of general goods and services and declines purchasing power, leading to crises (e.g. Azam and Khan, 2022; Atigala et al ., 2022; Nguyen et al ., 2022a, b).…”
Section: Methodsmentioning
confidence: 99%
“…Fidrmuc et al ., 2015; Berger and Sedunov, 2017; Beck et al ., 2022), affects bank capital (see, e.g. Horváth et al ., 2014; Evans and Haq, 2022), increases banks profitability (see, Duan and Niu, 2020; Nguyen et al ., 2022a, b; Kusi et al ., 2022) influences banks market power (see, Bawazira et al ., 2018; Dang, 2022; Nguyen et al ., 2022a, b). Many of these empirical studies focus on advanced countries with well-developed financial markets and banks (see, Berger and Bouwman, 2017; Berger et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%